Religious Communitarianism, Covenants, and Liberal Theory: On the Political Thought of Rabbi Lord Jonathan Sacks - Perez, Naḥshon (The review of faith & international affairs, 2023)
Lord Rabbi Sacks was a major religious Jewish figure. In this article, we examine his version of a covenant-based communitarianism. We begin with exploring Sacks’ social communitarian view, and his support of a covenant-based politics. We then turn to evaluate Sacks’ covenant-based view, and argue that while his social communitarian view is valuable and important, his covenant-based political view faces the same challenges that troubled communitarian views, namely the fact of religious, value, and ethnic plurality. One possible way forward is via a federalist system, in which covenants are localized.